Talent Management as an Introduction to Developing Institutional Performance in the Technical Colleges in Gaza Strip - Mansour Mohammed Ali Alayoubi; Moein Jihad Salman (University of Science and Technology, Yemen, 2020)
This study aimed to identify the role of talent management in developing institutional performance in technical colleges in Gaza Strip. To achieve the study objective, the descriptive analytical approach was used. The study population consisted of workers in supervisory positions in technical colleges in the Gaza Strip, where 5 colleges of 112 employees were included in the study. For selecting the study sample, the complete census method was used due to the small size of the study population. To collect data, questionnaires were distributed to the study sample, but 109 forms were returned (97.3%). The results of the study showed a significant degree of agreement in the dimensions of talent management in the technical colleges in Gaza Strip of a relative weight 71.70%. There was also a significant degree of agreement in the dimension of institutional performance of a relative weight 75.89%. There was also a statistically significant relationship between the dimensions of talent management and the development of institutional performance in technical colleges from the point of view of workers in supervisory positions. Further, there was a statistically significant effect at the level of significance (0.05 ≥α) between the dimensions of talent management (communication with talented workers, empowering, attracting and maintaining them) and developing institutional performance in the technical colleges in Gaza Strip; other variables had a weak impact. The study recommended that talented workers should be given more independence and empowerment and more opportunities to participate in decision-making regarding work. Attention should also be paid to infrastructure and technology, and the allocation of resources, both financial and human in order to contribute to the development of institutional performance in technical colleges.